The Authority of the Supervisory Board in Realizing the Principles of Good Corporate Governance Judging from the Law Number 21 of 2008 concerning Islamic Banking - Asmadi, Erwin (Inspiring Law Journal, 2022)
This research is a type of normative research that uses secondary data sources and analyzes data with qualitative analysis methods in the form of sentence descriptions that are easily understood by readers. Based on the results of the research that the Sharia Supervisory Board is usually placed at the level of the Board of Commissioners in each bank. This is to ensure the effectiveness of any opinion given by the Sharia Supervisory Board. Therefore, the determination of the members of the Sharia Supervisory Board is usually carried out by the General Meeting of Shareholders (GMS), after the members of the Sharia Supervisory Board have received a recommendation from the National Sharia Council. Whereas the authority of the Sharia Supervisory Board is to ensure and supervise the conformity of bank operational activities to fatwas issued by DSN, to assess sharia aspects of operational guidelines, and products issued by banks. That the role of the Sharia Supervisory Board is very important to carry out the principles of good corporate governance because those who deal with an Islamic bank need guarantees that the bank conducts transactions in accordance with Islamic law